Vigilantism and its Implications on Nigeria's National Security: A Case Study of Anambra Vigilante Group (A.V.G), 1998-2020 - Udeagbala, Lawrence Okechukwu; Ntukogu, Ozinna Tochukwu (NIU Journal of Social Sciences; Vol 8 No 2 (2022): NIU Journal of Social Sciences, Vol. 8 No. 2, June 2022DO - 10.58709/niujss.v8i2.1447, 2022)
A lot has been written on the security challenges facing Nigeria as a country and the lapses of the Nigeria Police in providing adequate security. These security lapses made some state governors to inaugurate quasi police outfits with different nomenclature to complement the activities of the police; yet, there is a vehement opposition for the establishment of a state owned police in Nigeria. One of the reasons often adduced for this opposition is that some state governors might use the state police to manhandle their oppositions. Extant works so far on this issue have neither adequately investigated the activities of these state and community created police outfits, nor have they comprehensively assessed the security implications of such groups to Nigeria's national security. This study therefore, is an examination of vigilantism in Anambra State of Nigeria, using one of these community created security outfits, the Anambra Vigilante Group (A.V.G).The paper argues that state and community created security groups like the AVG are already performing the anticipated functions of state police. From the findings of the study, there is no gainsaying that quasi police outfits such as AVG, have contributed immensely in ameliorating security challenges in Anambra State in particular and Nigeria at large; however, there are some challenges and security implications that come with the existence of an informal security outfit like the AVG. Using both primary and secondary sources of data generated from field research, the study employs both qualitative and quantitative methods of historical research. Keywords: Vigilantism, Security, National Security, Anambra Vigilante Group